SERVANT LEADERSHIP AND ITS INCIDENCE ON THE ORGANIZATIONAL PERFORMANCE OF ADMINISTRATION PROFESSIONALS IN PERU - Luciano Alipio , Rober Anibal (2022)
The objective of the research was to measure the incidence of leadership in organizational performance in administration professionals in Peru. The research had a quantitative approach, through a non-experimental cross-sectional design, with a causal explanatory scope. The sample consisted of 385 professionals registered in administration to whom a virtual survey was applied using a 58-item questionnaire that measures the variables; the data is processed using the statistical program SPSS; descriptive statistics and model of structural structures were performed. The results indicate that empowerment, authenticity, stewardship and responsibility, as dimensions of servant leadership, explain 79% of the behavior of the organizational performance variable.